PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK BESARAN FISIKA DAN SATUANNYA - Henok Siagian; Hunter Lumbanbatu (UNIVERSITAS NEGERI MEDAN, 2015)
This research aimed to determine the effect of Problem Based Learning Model on physics learning outcome of students in the subject physics mulberry and its unit in X class SMA Katolik Budi Murni 3 of Medan T.P 2013/2014. The kinds of this reaserch is quasi-experimental. The population in this research is all of the students of X class SMA Katolik Budi Murni 3 of Medan which consisting of 4 classes totally 130 sample students . the cluster random sampling was done by taking 2 classes of 4 classes are randomly. The class of X-2 as experiment class and X-4 as control class that each class is 34 and 36 students. The instrument used achievement test is a multiple-choice test consist of 10 questions that have fulfilled content validity. The eksperimental class treated by using Problem Based Learning Model and control class by using convensional model. Based on t test that Ha is accepted, it means that Problem Based Learning Model has significant impact in improving student learning outcomes. Keywords : Problem Based Learning Model, Studing Result and StudentActivity.